Fracture of polycrystalline graphene membranes by in situ nanoindentation in a scanning electron microscope - Suk, Ji Won; Mancevski, Vladimir; Hao, Yufeng; Liechti, Kenneth M.; Ruoff, Rodney S. (Physica status solidi. PSS-RRL. Rapid research letters, 2015)
Failure of polycrystalline graphene grown by chemical vapor deposition was investigated by nanoindentation in a scanning electron microscope. Circular graphene membranes were subject to central point loads using a nanomanipulator combined with an atomic force microscope cantilever as a force sensor. The grain boundaries of the polycrystalline graphene were visualized by Raman spectroscopy coupled with a carbon isotope labeling technique. Graphene membranes without any grain boundary had a failure strength of 45.4 ± 10.4 GPa, compared to 16.4 ± 5.1 GPa for those with grain boundaries when a Young's modulus was assumed to be 1 TPa. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) The failure strength of polycrystalline monolayer graphene grown by chemical vapor deposition is investigated by in situ nanoindentation in a scanning electron microscope. By visualizing the grain boundaries with carbon isotope labeling and Raman mapping techniques, the mechanical property of monolayer graphene is correlated with the grain boundary density.